Fluoroquinolone resistance in ESKAPE pathogens: evolutionary pathways, one health transmission, and clinical surveillance - Elbehiry, Ayman; Marzouk, Eman; Abalkhail, Adil (Frontiers in Microbiology, 2026)
Fluoroquinolones (FQs) remain important treatments for many Gram-negative and some Gram-positive infections, but rapid resistance development is steadily reducing their clinical usefulness. This review integrates biological and epidemiologic evidence through a One Health perspective focused on the ESKAPE group: Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. At the molecular level, resistance often begins with changes in quinolone-resistance determining regions of DNA gyrase and topoisomerase IV, followed by spread through plasmid-mediated mechanisms including qnr, aac(6′)-Ib-cr, qepA, and oqxAB. Species-specific efflux pumps such as NorA, AcrAB–TolC, and OqxAB, along with outer membrane and porin alterations, further contribute to resistance. Co-selection on mobile elements, including IncX, IncF, and IncL plasmids that may also carry ESBL or AmpC genes, enhances dissemination. Extrapatient reservoirs, including external hospitals, veterinary medicine, food-animal production, and contaminated water, sustain selection pressure and support horizontal transmission. Rising minimum inhibitory concentrations (MICs) are diminishing the reliability of empiric FQ therapy. Pharmacokinetics and pharmacodynamics are central to this trend; suboptimal exposure, such as ciprofloxacin AUC/MIC below 125 in Gram-negative infections, increases the time within the mutant-selection window and favors first-step mutants. Mechanism-based strategies include target-attaining dosing, early optimization of therapy, use of combinations that address efflux or permeability barriers, and stewardship guided by local MIC distributions. Emerging priorities include AI-based prediction of resistance trajectories, efflux and plasmid-transfer inhibitors, and phage or nanoparticle systems designed to reduce pathogen burden, disrupt biofilms, generate reactive oxygen species, or deliver site-directed therapy. Integration of rapid diagnostics will support these efforts and help preserve FQ effectiveness.